DEVELOPMENT OF A WARMING-UP GAME GUIDEBOOK FOR ELEMENTARY SCHOOL PHYSICAL AND SOCIAL SCIENCES LEARNING - Rizky Kurniawan,; Rahmat Sanusi,; Anggri Dwi Nata,; Hari Adi Rahmad, (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
The primary problem underlying this research is the lack of learning media related to warm-up using small games, and children’s lack of enthusiasm for unvaried warm-up. This research aims to develop a guidebook for small warm-up games for elementary school physical education. The research used R&D (research and development) using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The population in this study was 15 people. The sample selection used a saturated sampling technique involving 15 people. The data collection technique used an assesment questionnaire from the material, media, and user validators. To test the effectiveness of the product by looking at the T-Test, namely to see the difference in understanding of physical education teachers before and after using the product. The analysis technique used a likert scale as the assessment score scale and the average for the validation criteria using a percentage score. The validation result of the material expert obtained a score of 90% with a very appropriate statement. The validation result from the media expert obtained a score of 90% with a very appropriate statement. The result of the teacher’s response obtained a score of 82% with a very appropriate statement. The result of the effectiveness test showed that there was a significant influence of the use of the small warm-up game guidebook on the understanding of the KKG physical education teachers in the Meral-Meral Barat sub district with the result of the t-test count of 11,1142857143 which was greater than the t-table value (1,761).